2007
DOI: 10.2113/jeeg12.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Radar CMP Velocity Estimates Due to Survey Geometry, and Their Implication for Ice Water Content Estimation

Abstract: The accuracy of velocity determination from common mid-point (CMP) ground penetrating radar surveys has been assessed in the past and found to be sufficient for migration and depth determination. Increasingly, these velocities are also being used to quantify subsurface physical properties such as water content. This paper demonstrates that small errors in measured velocity can result in large errors in these derived properties. We have evaluated the size of some error sources with specific reference to a given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…We then used the synthetic traveltimes for calculating the reflector depths and the depth-averaged velocities (averaged from the surface to the reflector depths) subject to the NMO equations. Differences in depth-averaged velocities were smaller than 0.5 %, and differences in reflector depths were smaller than 0.5 m. Similar to the findings of Barrett et al (2007), this confirms that in our case the NMO approximation essentially holds, even for comparatively large horizontal offsets and a continuously changing depth-velocity function. This must not always be the case and ray tracing easily allows the NMO approximation to be checked for each specific setting.…”
Section: Benefits Of Traveltime Inversion Using Ray Tracingsupporting
confidence: 90%
“…We then used the synthetic traveltimes for calculating the reflector depths and the depth-averaged velocities (averaged from the surface to the reflector depths) subject to the NMO equations. Differences in depth-averaged velocities were smaller than 0.5 %, and differences in reflector depths were smaller than 0.5 m. Similar to the findings of Barrett et al (2007), this confirms that in our case the NMO approximation essentially holds, even for comparatively large horizontal offsets and a continuously changing depth-velocity function. This must not always be the case and ray tracing easily allows the NMO approximation to be checked for each specific setting.…”
Section: Benefits Of Traveltime Inversion Using Ray Tracingsupporting
confidence: 90%
“…6) was used to constrain the lateral extent of the intrusions. Blakely et al (2016) have also developed a method to retrieve the edge of a body and its depth (Fig. 5) by using the reciprocal of the horizontal gradient at the zero contour of the tilt derivative grid (Fairhead et al, 2008;Salem et al, 2007).…”
Section: -D Forward Modelsmentioning
confidence: 99%
“…Several studies have successfully performed this type of analysis [Murray et al, 2000, with colocated ice core measurements showing only small errors in EM wave speed (ranging from 1.4% to 5.7% depending on frequency) [Eisen et al, 2002]. Small uncertainties in EM wave speeds are especially important to inversions for water content in ice, as Barrett et al [2007] found that an 8% deviation in the EM wave speed results in an 80% error in inferred water content.…”
Section: Introductionmentioning
confidence: 99%